Identifikasi Klinik Pratama di Jawa Barat Terhadap Kenyamanan Psikologi Pengguna Ruang - Saragih, Veranita Br.; Rusyda, Hana Faza Surya; Anwar, Hendi (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2023)
As time goes by, the human population level is increasing. Likewise with the development and increasing number of health units, especially clinics where the increasing number of clinics will lead to quite tight competition between clinics. The clinic itself is divided into two types, namely the primary and primary clinics. The clinic to be identified this time is a primary type clinic in West Java Province. For this reason, the facilities and spatial atmosphere that are applied to the interior elements available in a clinic will have an impact on the comfort of room users so that the number of visitors or patients arriving will increase. The author uses a qualitative research method to examine the interior design of this building, in which this method examines several primary clinic interiors located in West Java. Primary clinics that will be identified have the same inpatient provision. So it can be seen that the Pratama clinic in West Java has not paid attention to the design of interior elements which will have an impact on the psychology of space users.